Nilai Sosial dan Budaya Tradisi Tedhak Siten Masyarakat Desa Kalangan, Ngunut, Tulungagung - Muhammad Za’im Mutahajjidir Rohim; Ananta Nur Aribyan; Sheila Monica Yulias Tanti; Hayyina Winda Tsaniya; Umi Nur Chofifah; Hany Nurpratiwi (Lembaga Pengembangan Kinerja Dosen, 2023)
The Tedhak siten tradition is one of the typical traditions of the Javanese people. Tedhak siten is a series of traditions from the birth of a baby. An expression of gratitude for the birth, safety, and growth and development of babies is embodied in this tedhak siten tradition. The tedhak siten tradition is also carried out to get rid of convulsions in babies. There are many social and cultural values ​​in the tedhak siten tradition that can form the basis of human behavior and can be used as role models in everyday life. The subject of this research is the people of Kalangan Village, Ngunut District, Tulungagung Regency. This is because the village is rich in culture and still preserves the tedhak siten tradition. This study discusses how the procession of the tedhak siten tradition and the cultural and social values ​​contained in a series of tedhak siten traditions is carried out by the people of Kalangan Village, Ngunut District. This study aims to find out about the tedhak siten procession in Kalangan Village and the meaning of its socio-cultural values. The method used in this journal research is descriptive qualitative research, where this research was conducted by interviews, field observations, and literature studies from various related journals. The tedhak siten procession in Kalangan Village includes, being ordered to step on the 7-colored jenang, climb the cane ladder, enter the chicken cage, choose a favorite object, grab coins or coins, bathe in flower water, and wear new clothes. Some of the values ​​contained in the tedhak siten tradition are self-confidence, generosity, always maintaining family honor, and diligent work.